Non-invasive predictors of survival in cardiac amyloidosis - Kristen, Arnt; Dengler, Jolanta; Schönland, Stefan; Hegenbart, Ute; Schnabel, Philipp Albert; Kristen, Joern H.; Goldschmidt, Hartmut; Katus, Hugo; Dengler, Thomas (European journal of heart failure, 2007)
Background: Patients with cardiac amyloidosis (CA) have increased mortality. Aims: Clinical, electrocardiographic, and echocardiographic parameters were assessed for risk-stratification of CA. Methods and results: CA was confirmed by endomyocardial biopsy in 59 patients (54.8±1.2 years) with light-chain (n = 43) or transthyretin amyloidosis (n = 16). Six patients without CA served as controls (NCA). Clinical symptoms, electrocardiographic, and echocardiographic parameters were analyzed for prognostic significance. Of the patients with light-chain amyloidosis, 14 died and 2 underwent heart transplantation. 1-/3-year survival was 68%/63%. Survival depended on left ventricular function (LV-EF), LV mass, radius/wall thickness, septum thickness, low voltage pattern (LVP), conduction delay, NYHA class, and stem cell transplantation. A multivariate model only contained LV-EF and LVP; the beneficial effect of stem cell transplantation was cancelled out as this treatment was withheld in patients with highest cardiac risk. Survival was most limited if both risk factors occurred. Cardiac involvement in transthyretin amyloidosis showed better survival (2 deaths, 1-/3-year survival 91%/83%). Analysis of prognostic risk factor utility in all amyloid patients (light-chain and transthyretin) again revealed LVP and LV-EF, and aetiology of amyloidosis as independent survival parameters. Conclusion: Prognosis of CA is poor, but aetiology of amyloid, LVP, and LV-EF allows identification of patients at highest risk of death, who may require individual treatment approaches (heart transplantation prior to causative therapy).
Available online 9 March 2007
Gesehen am 11.02.2022